PENGARUH KUALITAS LAYANAN DAN CITRA MEREK TERHADAP KEPUASAN PENGGUNA YOUTUBE PREMIUM MENGGUNAKAN PARTIAL LEAST SQUARE - Ajeng Dwi Rizkia; Dwi Ispriyanti; Sugito Sugito (Jurnal Gaussian, 2022)
As one of the largest digital service providers in the world, YouTube certainly makes breakthroughs to maintain user interest in accessing videos through YouTube, one of which is by creating the YouTube Premium service. This research was conducted to determine the extent to which these services can provide a sense of satisfaction for its users, because as a digital service provider company, YouTube is very dependent on user satisfaction. User satisfaction is influenced by service quality and brand image. In this study, service quality, brand image, and service user satisfaction act as latent variables. To test the predictive relationship between indicator variables and variables that cannot be measured directly (latent variables) by seeing whether there is a relationship or influence between these variables using the obtained modeling can be done using the Partial Least Square method. Therefore, to determine the effect of service quality and brand image on YouTube Premium user satisfaction, an analysis was conducted using the Partial Least Square method. The research data was obtained by distributing questionnaires to 150 YouTube Premium users in Indonesia. The results of the analysis show that service quality and brand image have a significant effect on YouTube Premium user satisfaction.